Eventos públicos e privados : a elaboração de políticas culturais voltadas para a realização da festa - Ribeiro Filho, José (2008)
The present work makes an analysis about the public politics of the state of Sergipe in the area of fomentation to the culture in the last three decades. These they are returns mainly for the accomplishment of large-scale events, in the which local artists are presented and of others states of the country. Our study this directed toward the actions of the State of the Secretary of State of the Culture, the Cultural Foundation of Aracaju FUNCAJU and the private foundations of culture that also develop a work of support to the production of the sergipanos artists. We do also make an analysis of the trajectory of the events carried out by the public initiative as the Festival of Art of Saint Cristóvão and the Cultural Meeting of Laranjeiras, of like these had arrived in those communities and which the main changes that happened in their format. To understand the organizational structure of these two events we make a comparative analysis with the Pre-Caju, event that is promoted by the private initiative in partnership with agencies of the State and the City of Aracaju.